A HU‐like protein is required for full virulence in Xanthomonas campestris pv. campestris. (23rd August 2021) - Su, Qian; Wang, Xin‐Xin; Leng, Ming; Qi, Yan‐Hua; Pang, Fu‐Yuan; Tang, Ji‐Liang; Lu, Guang‐Tao
Abstract: Bacteria harbour several abundant small DNA‐binding proteins known as nucleoid‐associated proteins (NAPs) that contribute to the structure of the bacterial nucleoid as well as to gene regulation. Although the function of NAPs as global transcriptional regulators has been comprehensively studied in the model organism Escherichia coli, their regulatory functions in other bacteria remain relatively poorly understood. Xanthomonas campestris pv. campestris (Xcc) is a gram‐negative bacterium that causes black rot disease in almost all members of the crucifer family. In previous work, we demonstrated that a Fis homologue protein, which we named Fis‐like protein (Flp), contributes to the regulation of virulence, type III secretion, and a series of other phenotypes in Xcc. Here we have examined the role of XC_1355, which is predicted to encode a DNA‐binding protein belonging to the HU family herein named HU‐like protein (Hlp). We show that mutation of XC_1355 in Xcc reduces the virulence, extracellular polysaccharide production, and cell motility, but has no effect on the production of extracellular enzymes and induction of the hypersensitive response. These data together with transcriptome analysis indicate that hlp is a previously uncharacterized gene involved in virulence that has partially overlapping and complementary functions with flp in Xcc, although the two regulators have opposite effects on the expression of genes involved in type III secretion. The findings add to our understanding of the complex regulatory pathways that act to regulate virulence in Xcc. Abstract : A previously uncharacterized protein, Hlp, is involved in virulence and has opposite effects on the expression of type III secretion proteins compared with Flp.